Factors affecting physical activity in premarital women of childbearing age in Semarang City - Hema Dewi Anggraheny; Aisyah Lahdji; Merry Tiyas Anggrainy; Tessa Rahma Adila (Universitas Gadjah Mada, 2025)
Purpose: Physical activity is one of the pillars of implementing balanced nutrition, which is the foundation of healthy living, especially for women of childbearing age (WCA). This study analyzes the factors influencing physical activity in premarital WCA. Methods: This research employs a quantitative, cross-sectional design. The sample comprised 160 premarital women of childbearing age from 10 Semarang Health Centers across nine districts, and the study was conducted from November 2024 to January 2025. The tests conducted were the Mann-Whitney and Chi-square tests. Results: The prevalence of physical activity among premarital WCA included physical activity not adhering to the guidelines at 129 (80.6%) and those following the procedures at 31 (19.4%). The relationship between knowledge (p = 0.493), attitude (p = 0.980), education (p = 0.236), regular exercise patterns (p = 0.002), availability of facilities (p = 0.017), availability of transportation (p = 0.447), family support (p = 0.922), and friend support (p = 0.937) to physical activity was analyzed. Conclusion: Most WCA do not meet the physical activity standards according to the guidelines. The presence of a consistent exercise pattern and access to sports facilities are factors that influence meeting the physical activity standards in premarital women. Public health efforts should focus on facilitating regular exercise routines and improving access to safe, appropriate sports facilities for women.